Tindakan Pencemaran Nama Baik Melalui Media Sosial Dalam Perspektif Hukum Pidana - Wahyudi, Rifal (Universitas Islam Indragiri, 2024)
Indonesia has entered the era of globalization where various kinds of growth and development in various sectors are quite developed, especially in terms of information technology, the era of globalization requires people to be free to do various things including free to express themselves and free to argue, so that there needs to be rules in terms of using social media and the internet. And in this case the author is interested in making a scientific work in the form of a journal in which the research method used by the author is to use the literature method and the literacy of this research is in the form of books, journals, reports and even newspapers. The formulation of the problem in writing this journal is (1) what is meant by defamation via the internet or social media, (2) how is the view of criminal law on defamation cases committed on the internet or social media and (3) what are the threats to perpetrators of criminal defamation on social media. And the conclusions are (1) defamation is an act that deliberately makes a person's good name or reputation tarnished or bad, so that it can kill the mentality and characteristics that have been previously known to the person to be bad, (2) according to the view of criminal law defamation is included in the realm of criminal law if it disturbs the public interest and causes chaos in society, and according to criminal law defamation is included in the offense of complaint, where this offense will only be processed by the police if there is a complaint from the victim, (3) in criminal law in Indonesia this defamation case has been regulated in the ITE Law, contained in Law No. 11 of 2008 which was later amended in Law No. 19 of 2016 concerning Information and Electronic Transactions. The threats for the perpetrators of insults and defamation committed online will be subject to a maximum fine of Rp. 750 million and a maximum imprisonment of 4 years.